Inhibition of Autophagy in Heat-Stressed Sperm of Adult Mice: A Possible Role of Catsper1, 2 Channel Proteins - Malihe Soltani; Majid Rahmati; Mohammad Reza Nikravesh; Shahin Saeedi Nejat; Mahdi Jalali (Journal of Tropical Medicine)
Objective. Various phenomena guarantee gamete maturation and formation at all stages of evolution, one of which is autophagy playing a critical role in the final morphology of gametes, particularly sperms. Autophagy is influenced by oxidative stress, disturbances of calcium homeostasis, and hyperthermia conditions. The current study aimed to assess the autophagy-related proteins along with the activity of sperm calcium channel (CatSper) proteins following the induction of heat stress (HS). Methods. The study sample includes two groups of adult mice: sham and HS groups. In the HS group, the right testis was transferred to the abdominal cavity for 120 hours and then returned to the scrotum where it remained for 7 days. After 7 days, the testis and epididymis were removed to conduct real-time, immunohistochemical studies, sperm parameter evaluation, and seminiferous tubule assessment. In this study, the expression and distribution of autophagy proteins were measured. Plus, CatSper1 and CatSper2 were evaluated as proteins of calcium channels. Results. The results of the present study demonstrated that the expression intensity of autophagy indices in seminiferous tubules decreased significantly after HS induction, which was associated with a decrease in the distribution of CatSper proteins in the sperms. HS led to morphological changes in sperm, reduced motility and viability of sperm, and decreased spermatogenesis indices. Conclusion. In this study, following heat stress, the decrease in CatSper protein distribution may lead to the structural disorder of CatSper channels, which could strongly affect autophagic activity. Also, disruption of spermatogenesis and sperm parameters may be the consequence of decreased autophagy activity.